The impact of Sejingkat coal-fired power plant on fish fauna and fisheries in Sungai Sarawak - Jubin, Ak Hilton Muda (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Study on the impact of Sejingkat Coal-fired Power Plant on the fish fauna and fisheries of Sungai Sarawak was carried out in December 2005 until March 2006. Sejingkat Coal-Fired Power Plant is the first project of it type in Sarawak and is operated for electricity need of industries in Kuching. This study was carried out through sampling of fish fauna and survey based on questionnaires carried out on the local inhabitants of Kampung Senari, Kampung Goebilt and Kampung Muara Tebas. A total of 22 species of fish from 18 families and 4 species of crustacean from 2 families were recorded from Sungai Sarawak. A daily catch of 170 kg was reported for Kampung Senari, 785 kg for Kampung Goebilt and 870 kg for Kampung Muara Tebas. The result showed that there is minimal impact of Sejingkat Coal-Fired Power Plant on the fish fauna and fisheries of Sungai Sarawak. It could be postulated that the water used in the cooling of the turbine system and then discharged into Sungai Sarawak did not have significant impact on the aquatic life in Sungai Sarawak. Therefore, impacts, if any are localized to a small area closed to the discharge outlet. This may be due largely to the tidal influence of Sungai Sarawak whereby heated water discharge into the river is well diluted.